2020
DOI: 10.4082/kjfm.18.0148
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Living Alone and Smoking and Alcohol Consumption in Korean Adults

Abstract: Background: Recently, single-person households have increased in Korea and this trend may have potential public health implications and affect various health behaviors. This study investigated the associations between living alone and health behaviors such as smoking and alcohol consumption among Korean adults. Methods: We used data from the 6th Korea National Health and Nutrition Examination Survey between 2013 and 2015 and a total of 17,088 adults were included. We performed a multivariable logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Firstly, the association might not be causal, but rather because younger adults who live alone have greater exposure to vascular factors, such as smoking, drinking, eating salty foods, lower consumption of some core foods groups (vegetables, fruits, and seafood) and physical inactivity. 39 , 40 Compared to older adults who lived alone, younger adults living alone had higher proportions of smoking 41 and lower vegetables intake. 42 In comparison to those to those living with others, older adults who live alone may be physically healthier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the association might not be causal, but rather because younger adults who live alone have greater exposure to vascular factors, such as smoking, drinking, eating salty foods, lower consumption of some core foods groups (vegetables, fruits, and seafood) and physical inactivity. 39 , 40 Compared to older adults who lived alone, younger adults living alone had higher proportions of smoking 41 and lower vegetables intake. 42 In comparison to those to those living with others, older adults who live alone may be physically healthier.…”
Section: Discussionmentioning
confidence: 99%
“…It it also possible that living alone has a causal relation with mortality. Individuals who live with others may gain more encouragement to maintain a healthy lifestyle, and this may be more important in younger individuals 41 , 42 and in males. 39 , 45 Further, individuals who live with others may get faster contact with medical services and first aid help in the event of illness, though it seems implausible that this factor would differ by age or sex.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers living alone were more likely to develop MACEs because smokers living alone smoked more cigarettes than those living with others ( 19 ). Complex factors associated with living alone may explain why recent studies have reported discordant results regarding the outcomes of patients who live alone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that stress acts as a major determinant of the incidence and frequency of smoking [32]. Stress is often cited as the main factor that drives adolescents to attempt smoking [33], and mood improvement, that is, stress reduction, is cited as the main reason for smoking [34].…”
Section: Discussionmentioning
confidence: 99%